Analisis Kepatuhan Wajib Pajak Pasca Implementasi Kebijakan Tax Amnesty - Situmorang, Dokman Marulitua; Pratama, Eri (Universitas 17 Agustus 1945 Jakarta, 2022)
The goal to be achieved is to find out the relationship between the implementation of the tax amnesty policy and taxpayer compliance and to find problems implementing the tax amnesty policy and find the right solution so that the expected goals can be implemented properly. The method used is a quantitative and qualitative method that seeks to link the existing facts with various applicable regulations so that an overview of taxpayer compliance will be obtained. The data taken is secondary data which is processed in the form of the number of registered taxpayers, the number of taxpayers who are required to report tax returns (SPT) and the realization of SPT reporting.The method used is a quantitative and qualitative method that seeks to link the existing facts with various applicable regulations so that an overview of taxpayer compliance will be obtained. The data taken is secondary data that is processed in the form of the number of registered taxpayers, the number of taxpayers who are required to report the Tax Return (SPT) and the realization of SPT reporting.The results show that the tax amnesty policy has a significant effect on compliance in general shortly after the policy is enacted. However, if it is detailed on corporate taxpayer compliance, non-employee individuals and employee individuals in general have no significant effect. Suggestions to be conveyed from this research are 1) the Directorate General of Taxes must continue to strive to improve services, supervision and guidance to taxpayers 2) The Directorate General of Taxes must continue to improve itself through tax reform 3) The government must be firm in implementing regulations governing sanctions for taxpayers who do not participate in the tax amnesty program.